Performance of 60-day Cowpea in the Fields of Uttarakhand Farmers: An Adoption Study - Surya Rathore, (Indian Journal of Extension Education, 2017)
Farmer participatory trials of Pant Lobia 1, 2 &3 varieties of '60-days cowpea' were conducted on 236 farms inUttarakhand and it was found through interviews and focused group discussions conducted on farmers' fields that 60-daycowpea was short duration variety. Pant lobia 2 was more accepted as vegetable. Farmers had adopted simple practiceslike sowing time and method; harvesting and storage; selection and preparation of field and selection of variety. Butimportant practices involving skills like weeding, disease and insect and pest management; seed treatment, fertilizer andnutrient management and irrigation were adopted by relatively less percentage of farmers. Majority of farmers hadmedium level of adoption of cowpea production technology and faced constraints like lack of knowledge about plantprotection measures. Problem of land fragmentation was more severe in hills as compared to plains where prevalence ofpests and diseases was more. It is implied that cooperative farming should be done in hills and specialized one daytrainings can be organized by extension agencies on specific problems